Efektivitas Media Vascak Physics Animation untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Rangkaian Listrik Searah - Fitri, Noer; Firmansyah, Juli (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2025)
The aim of this research is to increase students' conceptual understanding of one way electric circuit material using the Vascak Physics Animation media. The subjects of this research were students from one of the classes at the Bekasi School, consisting of 13 students and 17 female students. This type of research is a quasi-experiment with a before-after design. Data analysis using a paired sample t-test based on pretest and post test data shows that there is a significant difference between before using Vascak Physics Animation with an Asiymp.Sig (2- Tailed) significance value of 0,000 and after using Vascak Physics Animation and the results of the average value The average Normalized Gain (N-Gain) is 0,41 in the medium classification so that it can be concluded that there is an influence of using the Vascak Physics Animation online media on students' conceptual understanding and the use of the Vascak Physics Animation learning media shows that it is effective in increasing students' conceptual understanding of unidirectional electric circuits material.